The Impact of Technological Complexity and Interfirm Cooperation on Business Survival - Singh, Kulwant (Academy of Management Journal, 1997)
This study's predictions are that businesses developing high-complexity technologies face higher risks of failure than other businesses because of greater competency demands and higher organization costs. Further, alliances moderate such failure risks but provide fewer survival benefits for businesses commercializing less complex technologies. Hypotheses were tested with longitudinal data from the U.S. hospital software industry. High-complexity technology was associated with higher risk of failure, and alliances only partially moderated such risk.